Peran Pemuda dalam Optimalisasi Branding Desa Wisata Edukasi Toleransi - Alfaqi, Mifdal Zusron (Universitas Negeri Malang, 2022)
This study aimed to analyze the value of tolerance in religious diversity in Sukodadi Village and the role of youth in optimizing Sukodadi Village as a tolerant educational tourism village. This study was a qualitative approach with an intrinsic case study type of research. Informants were selected through a purposive sampling technique. Data collection techniques utilized interviews, observation, and documentation. Data were analyzed using the Robert K. Yin technique, including preparing propositions, comparing cases and initial propositions, correcting statements, and repeating the process until accurate data were found. The study results showed that the religious diversity and tolerance attitude of the people of Sukodadi Village had become a pilot as a tolerance education tourism village. The Sukodadi Village community, which has a diversity of religions, maintained conduciveness and harmony. As the nation's next generation, youth can take on a role by making Sukodadi Village a tolerance education tourism village through a tourism village branding strategy. The involvement of youth impacted village development and created an image of the village as a medium for educating tolerance for other villages in building tolerance in diversity.